Paraguay : Sixth Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2006)
Paraguay's Sixth Review Under the Stand-By Arrangement reports that the program is ending successfully, having achieved the broad objectives of restoring stability and beginning a process of structural reform, albeit with some delays. At the time of program approval in 2003, Paraguay had been experiencing one of the most severe financial and budgetary crises, triggered by the regional crisis of 2002 and exacerbated by weak macroeconomic fundamentals. A quick and decisive policy response, articulated in the context of the IMF-supported program, stopped the financial crisis and put the public finances on a sustainable path.